PENGARUH PERILAKU KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KOMITMEN ORGANISASI WIDYAISWARA PADA BADAN PENGEMBANGAN SUMBER DAYA MANUSIA (BPSDM) KEMENTERIAN ENERGI DAN SUMBER DAYA MINERAL - Ahmad Khulaemi (Universitas Negeri Jakarta, 2017)
The objective of this research is find out the effect of leadership behavior and work environment on lecturer’s organization commitment. This research was conducted at agency of human resources development, ministry of energy and mineral resources. This research was using a survey method with path analysis applied in testing hypothesis and 63 samples selected by simple random sampling. The research technique is analysis with quantitative research approaches by using causal analysis. The finding of the research are: (1) there is a positive direct effect of leadership behavior on organization commitment; (2) ) there is a positive direct effect of work environment on organization commitment; (3) ) there is a positive direct effect of leadership behavior on work environment.